Luxation injuries in primary teeth: a retrospective study in children assisted at an emergency service - da Silva Assuncao, Luciana Reichert (2011)
The purpose of this study was to analyze luxation injuries in children between the ages of 0 and 5 years treated at an emergency service department. A total of 1,703 records, corresponding to a period of 10 years at the Emergency Center of the Baby Clinic at Londrina State University, Brazil, were analyzed. The age, gender, etiologic factors, type of injury, injured teeth, treatment and time interval between injury and treatment were determined for each patient. of the examined records, 409 patients met the study criteria and included a total of 679 injured teeth. Statistical analyses were carried out using the chi-square test with the level of significance set at 5%. Trauma incidence was higher in boys (57.0%) and in children less than two years of age (40.3%). Falling while walking or running was the most predominant etiologic factor (37.7%), and the most prevalent type of injury was subluxation (32.6%). Luxation injuries decreased with increasing age (p = 0.045). Treatment usually occurred within the first 1-15 days and was significantly associated with the type of trauma (p = 0.041). "Monitor only" was the treatment most frequently observed (74.0%). In conclusion, more luxation injuries were found in younger children, predominantly in boys. Falls resulting from walking or running were the etiologic factor most observed, with subluxation as the most common type of trauma. Treatment usually occurred within the first 15 days after the injury. Despite the severity of these injuries, "monitor only" was the eligible treatment.